2013
DOI: 10.1111/jpn.12062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eccentric exercise on branched‐chain amino acid profiles in rat serum and skeletal muscle

Abstract: Supplementation of branched-chain amino acid (BCAA) is often used to attenuate exercise-induced skeletal muscle damage and promote adaptation, but no definitive conclusion on the benefits of BCAA on muscle recovery after injurious exercise can be drawn. Exploration of the systematic BCAA alteration in muscular injury-repair stage per se without any BCAA supplement should provide some useful information in favour of BCAA application in muscle regeneration after injury. One bout of 90-min downhill-running exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…The comprehensive serum metabolite signatures induced by acute resistance exercise include decreased amino acids and increased fatty acids. These findings are consistent with previous observations that the oxidation and catabolism of amino acids, especially branched-chain amino acids (BCAA), are promoted by exercise (Qun et al, 2014), while the mobilization of free fatty acids from depots and efflux of plasma free fatty acids are increased by exercise (Friedberg et al, 1963;Shimomura et al, 2004). Importantly, the metabolites of valine, i.e., alpha-ketoisovaleric acid (akeval) and 2-hydroxy-3-methylbutyric acid (2H3MA), as well as a metabolite of alanine, pyruvic acid (Pyr), were also increased after acute exercise.…”
Section: Discussionsupporting
confidence: 93%
“…The comprehensive serum metabolite signatures induced by acute resistance exercise include decreased amino acids and increased fatty acids. These findings are consistent with previous observations that the oxidation and catabolism of amino acids, especially branched-chain amino acids (BCAA), are promoted by exercise (Qun et al, 2014), while the mobilization of free fatty acids from depots and efflux of plasma free fatty acids are increased by exercise (Friedberg et al, 1963;Shimomura et al, 2004). Importantly, the metabolites of valine, i.e., alpha-ketoisovaleric acid (akeval) and 2-hydroxy-3-methylbutyric acid (2H3MA), as well as a metabolite of alanine, pyruvic acid (Pyr), were also increased after acute exercise.…”
Section: Discussionsupporting
confidence: 93%
“…The comprehensive serum metabolite signatures induced by acute resistance exercise include decreased amino acids and increased fatty acids. These findings are consistent with previous observations that the oxidation and catabolism of amino acids, especially branched-chain amino acids (BCAA), are promoted by exercise (Qun et al, 2014), while the mobilization of free fatty acids from depots and efflux of plasma free fatty acids are increased by exercise (Friedberg et al, 1963; Shimomura et al, 2004). Importantly, the metabolites of valine, i.e., alpha-ketoisovaleric acid (α-keval) and 2-hydroxy-3-methylbutyric acid (2H3MA), as well as a metabolite of alanine, pyruvic acid (Pyr), were also increased after acute exercise.…”
Section: Discussionsupporting
confidence: 92%
“…Three BCAA (valine, leucine, and isoleucine) were increased by both GW501516 and training. Long-distance running involves mobilization of BCAA 29 and many studies demonstrate that BCAA concentrations immediately after exercise are reduced in the serum, but not in muscle 30 . We found that training or GW501516 treatment, preserved serum BCAA levels after exhaustive running.…”
Section: Discussionmentioning
confidence: 99%